POTENSI BUBUK TAPE KETAN (Oryza sativa glutinosa) PROBIOTIK SEBAGAI BAHAN MINUMAN FUNGSIONAL - , ASRI NURSIWI, Prof.Dr.Ir Endang S. Rahayu, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Probiotic is life microorganisms which when consumed in adequate amounts confer a health benefit on the host. Probiotics need a âvehicleâ for their specialized actions in gastrointestinal tract. In this reasearch, tape ketan was used as âvehicleâ. The objective of this research was to produce probiotic tape ketan powder as an ingredient of functional beverage. Tape ketan was made by fermentation of glutinous rice with ragi and supplemented with Lactobacillus plantarum Dad 13 (107 CFU/g glutinous rice) and than incubated at room temperature for three days. Probiotic tape ketan powder was obatained by spray dryer with inlet temperature 90oC and added maltodextrin into tape extract at concentration 35% (w/v). The powder was reconstituted into water with addition pectin and sucrose. The results showed that viability of lactic acid bacteria and L. plantarum decreased after drying (0,82 and 0,90 log cycle respectively) with viable count from 1,29 x 1010 CFU to 1,96 x 109 CFU for lactic acid bacteria and from 1,04 x 1010 CFU to 1,32 x 109 CFU for L. plantarum. It was reconstituted the powder at concentration 20% (w/v), added pectin at concentration 0,5% (w/v), and added sucrose at concentration 4% (w/v) to obtained probiotic tape ketan beverage. Tape ketan powder which was supplemented with probiotic Lactobacillus plantarum Dad 13 had potency as an ingredient of functional beverage ( from the viability after drying).